Dimensional optimization of a micro-channel heat sink using Jaya algorithm - Rao, R.V.; More, K.C.; Taler, J.; Ocłoń, P. (Applied thermal engineering, 2016)
Flowchart of Jaya algorithm. [Display omitted] •A new optimization algorithm named as ‘Jaya algorithm’ is proposed.•Two case studies of dimensional optimization of a micro-channel heat sink are presented.•Two objective functions of thermal resistance and pumping power are considered.•The results are compared with those obtained by MOEA, TLBO and numerical analysis.•The results obtained by Jaya algorithm are found better than the other approaches. In this paper, a recently proposed optimization algorithm named as ‘Jaya algorithm’ is used for the dimensional optimization of a micro-channel heat sink. Two case studies are considered and in both the case studies two objective functions related to the heat transfer and pressure drop, i.e. thermal resistance and pumping power, are formulated to examine the performance of the micro-channel heat sink. In the first case study, two non-dimensional design variables related to the micro-channel depth, width and fin width are chosen and their ranges are decided through preliminary calculations of three-dimensional Navier–Stokes and energy equations. In the second case study, three design variables related to the width of the micro-channel at the top and bottom, depth of the micro-channel and width of fin are considered. The objective functions in both the case studies are expressed in terms of the respective design variables and the two objectives are optimized simultaneously using the proposed Jaya algorithm. The results are compared with the results obtained by the TLBO algorithm and a hybrid multi-objective evolutionary algorithm (MOEA) and numerical analysis. The results obtained by the application of Jaya algorithm are found much better than those reported by the other approaches.